In House Training Game Edukatif Berbasis Android Bagi Calon Guru SD Se-NTB - Nurwahidah, Nurwahidah; Suranti, Ni Made Yeni; Ibrahim, Ibrahim; Alimuddin, Nurkhaerat (Indonesian Journal of Education and Community Services, 2024)
Community service activities entitled "In House Training of Android-Based Educational Games for Prospective Elementary School Teachers throughout NTB" aim to improve the understanding and technical skills of prospective elementary school teachers in using and utilizing educational game platforms, such as Wordwall and Quizizz, in the learning process. This training was carried out using a hybrid method, involving 50 participants consisting of prospective elementary school teachers throughout NTB, where 30 people participated online and 20 people offline. This training was held in response to the limited technical skills of prospective teachers in developing educational games, which were caused by the lack of information and training related to game integration in learning. The results of the training showed that participants succeeded in creating educational games using the platform that had been introduced. The success of this training emphasized the importance of developing the technical skills of prospective elementary school teachers in creating interactive learning media. It is hoped that similar training can be carried out more widely and sustainably to support improving the quality of learning in elementary schools